Island of dragons / 7. - McMann, Lisa (Unwanteds, 2016)
"Head mage Alexander Stowe and his friends successfully fended off the latest threat to their magical world of Artimé with the help of a surprise ally. But old enemies have secretly been plotting against them. Now Alex must lead his people in a final epic battle, one they can't hope to win alone"--Provided by publisher.